Shelf Life Estimation of Instant Noodle from Sago Starch and Catfish (Pangasius sp.) Using Accelerated Method - Harapan Siregar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research purpose was to estimate the shelf life of noodle from sagostarch and catfish (Pangasius sp.). Shelf life is one of the requirements that mustbe met before marketing of food products. Shelf life estimation was using theaccelerated method of observation of instant noodles for 28 days at three differenttemperatures namely 35°C, 45°C and 55°C. Parameters observed during thestorage process were the assessment of sensory level of rancidity and TBA value.Results show that shelf life of sago instant noodle by organoleptic assessment was35,81 days and the shelf life of sago instant noodle by TBA value was 44,85 daysat a temperature of 27oC. For food quality and safety reason, the shorter shelf lifeperiod (35,81 days) was choosen as shelf life of sago instant noodle.Keyword : sago, catfish, noodle, shelf life, accelerated method